Managerial perceptions of leadership and management in an African public service organization - Jones, Merrick L.; Sharma, Keshav C.; Blunt, Peter (1996)
This article describes and analyses data on perceptions of leadership and management, generated by a study of managerial behaviour, organizational functioning and performance in the Ministry of Local Government, Lands and Housing (MLGLH) in Botswana. The study was commissioned by the Swedish International Development Agency (Sida). The findings indicate that the managers in the investigation did not generally recognize the distinction between organizational leadership and management that is postulated in the predominant current western view. The perceived ideal leader who emerges from the investigation is kindly and supportive and provides clear directions; the western ideal of the `corporate hero' did not emerge from the findings. Further, the Tswana managers emphasize the reaction of the boss as a major factor in judging their own performance. This finding of the acceptance of hierarchical authority and accompanying dependency supports evidence from the few empirical studies undertaken previously in Africa, and has implications for the current plan to implant elements of the `Singaporean model' in Botswana. - Reproduced
Keywords: Management - Africa; Leadership - Africa; Public administration - Africa; Leadership; Civil service - Africa; Civil service